Réponses

Meilleure réponse !
2014-05-04T09:03:30+02:00
Bonjour,

Exercice 1

1) A=(\dfrac{3}{4})^2-\dfrac{1}{4}\\\\A=\dfrac{9}{16}-\dfrac{4}{16}\\\\\boxed{A=\dfrac{9}{16}}\\\\B=\dfrac{5}{4}-\dfrac{2}{3}\times\dfrac{9}{16}\\\\B=\dfrac{5}{4}-\dfrac{1}{3}\times\dfrac{9}{8}\\\\B=\dfrac{5}{4}-\dfrac{1}{1}\times\dfrac{3}{8}\\\\B=\dfrac{10}{8}-\dfrac{3}{8}\\\\\boxed{B=\dfrac{7}{8}}

C=\sqrt{96}+5\sqrt{6}-3\sqrt{150}\\\\C=\sqrt{16\times6}+5\sqrt{6}-3\sqrt{25\times6}\\\\C=\sqrt{16}\times\sqrt{6}+5\sqrt{6}-3\times\sqrt{25}\times\sqrt{6}\\\\C=4\sqrt{6}+5\sqrt{6}-3\times5\times\sqrt{6}\\\\C=4\sqrt{6}+5\sqrt{6}-15\sqrt{6}\\\\\boxed{C=-6\sqrt{6}}

Exercice 2

D = (3x - 4)² - x(3x - 4)

1) D = (3x - 4)² - x(3x - 4)
D = 9x² - 24x + 16 - 3x² + 4x
D = 6x² - 20x + 16

2) D = (3x - 4)² - x(3x - 4)
D = (3x - 4)(3x - 4) - x(3x - 4)
D = (3x - 4) [(3x - 4) - x]
D = (3x - 4)(3x - 4 - x)
D = (3x - 4)(2x - 4)
D = (3x - 4)*2(x - 2)
D = 2(3x - 4)(x - 2)

3) (3x - 4)(2x - 4) = 0
3x - 4 = 0  ou  2x - 4 = 0
3x = 4   ou  2x = 4
x = 4/3   ou   x = 4/2
x = 4/3   ou   x = 2
S = {4/3 ; 2}

Exercice 3

f(x) = 3x² - 5

1) a) f(0) = 3*0² - 5
f(0) = 0 - 5
f(0) = -5

L'image de 0 par la fonction f est égale à -5

b) f(-2) = 3*(-2)² - 5
f(-2 = 3*4 - 5
f(-2) = 12 - 5
f(-2) = 7

L'image de -2 par la fonction f est égale à 7

c) f(√3) = 3*(√3)² - 5
f(√3) = 3*3 - 5
f(√3) = 9 - 5
f(√3) = 4.

L'image de √3 par la fonction f est égale à 4.

2) Résoudre f(x) = 22
3x² - 5 = 22
3x² = 22 + 5
3x² = 27
x² = 27/3
x² = 9
x² - 9 = 0
x² - 3² = 0
(x - 3)(x + 3) = 0
x - 3 = 0   ou  x + 3 = 0
x = 3  ou  x = -3
S = {3 ; -3}